2021
DOI: 10.1021/acsomega.1c01524
|View full text |Cite
|
Sign up to set email alerts
|

Effective Halogen- and Phosphorus-Free Polyphenylene Ether Resin-Based Flame-Retardant Foam

Abstract: A novel halogen- and phosphorus-free intrinsic flame-retardant foam is fabricated from curable phenol-terminated polyphenylene ether resin with a high molecular weight using phenol, formaldehyde, and diphenyl ether as starting materials. The limiting oxygen index (LOI) of the pure foam is 24.90% ± 0.28. When 0.5 wt % silica sol is added, the LOI of the foam (SPF-0.5) is up to 28.5% ± 0.15 and both the combustion heat release rate and total combustion heat are low. Moreover, the SPF-0.5 foam exhibits high carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It can be found that the limiting oxygen index of PF and PUF were the same, while PAF improves the limiting oxygen index and the flame retardant performance of PF. Compared with a novel halogen and phosphorus‐free intrinsic flame‐retardant foam made by Li et al, the limiting oxygen index of PAF is increased by 48.60% 67 . The reason is that ammonium chloride acts as a halogen flame retardant.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It can be found that the limiting oxygen index of PF and PUF were the same, while PAF improves the limiting oxygen index and the flame retardant performance of PF. Compared with a novel halogen and phosphorus‐free intrinsic flame‐retardant foam made by Li et al, the limiting oxygen index of PAF is increased by 48.60% 67 . The reason is that ammonium chloride acts as a halogen flame retardant.…”
Section: Resultsmentioning
confidence: 93%
“…Compared with a novel halogen and phosphorus-free intrinsic flame-retardant foam made by Li et al, the limiting oxygen index of PAF is increased by 48.60%. 67 The reason is that ammonium chloride acts as a halogen flame retardant. In the case of high temperature or burning, the hydrogen chloride gas generated by the decomposition of ammonium chloride eliminates the active free radicals generated by the combustion of PF.…”
Section: Cone Calorimeter and Limiting Oxygen Index Analysismentioning
confidence: 99%